Enrichment, isolation and optimization of lipase-producing Staphylococcus sp. from oil mill waste (Oil cake) - Kumar, Ajit; Parihar, Surendra S; Batra, Nisha (Journal of Experimental Sciences, 2013)
The production of commercial enzymes, including lipase from bacteria has always been the industrial choice due to its economical and commercial feasibility. Twelve samples of oil cakes were enriched to isolate lipase producing bacteria and were screened for their lipolytic activity. The best producer (OC2) was characterized and identified as Staphylococcus sp. and was studied for lipase activity. The culture conditions were optimized for maximum enzyme production by isolate OC2 and were found to be 400C at pH of 7.0 with agitation of 140 rpm and 48 hours of incubation time for achieving maximum enzyme activity of 13.92 U/ml in crude enzyme extracts and 34.78U/ml after partial purification of enzyme, with about 80% enzyme recovery. The purified enzyme showed maximum enzyme activity at 400C and pH 7.0. The study provides a good mesophilic bacterial candidate for potential industrial production of lipase.